1991
DOI: 10.1093/ajcn/53.6.1493
|View full text |Cite
|
Sign up to set email alerts
|

Long-term memory of body weight and past weight satisfaction: a longitudinal follow-up study

Abstract: Recalled body weight and self-reported current weight were validated in a longitudinal study population by comparing recalls at 50 y to actual measures taken at ages 18, 30, 40, and 50 y. Recalled body weights were also compared with reported desired weights at these same ages. Self-reported weights at 50 y were equally accurate for both males and females; the mean reporting underestimate was -1.98 kg for males and -1.86 kg for females. Males' self reports at age 50 y were influenced by years of education (P l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(142 citation statements)
references
References 42 publications
7
134
1
Order By: Relevance
“…Nonetheless, research on the validity of long-term recall of body weight supports the relative accuracy and usefulness of such data as a proxy for measured weight in epidemiologic studies, and corroborates its predictive utility. [59][60][61][62] For example, Casey et al 60 found that, among 50-year-old participants, the accuracy of recalled height and weight measured in childhood, adolescence and at ages 30 and 40 did not differ significantly from the accuracy of current self-reported height and weight that also was measured at the same time. Similarly, Norgan and Cameron 62 reported that recall of previous height and weight over a 27-to 37-year interval (measured at 18 to 24 years old) was not significantly influenced by the passage of time.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, research on the validity of long-term recall of body weight supports the relative accuracy and usefulness of such data as a proxy for measured weight in epidemiologic studies, and corroborates its predictive utility. [59][60][61][62] For example, Casey et al 60 found that, among 50-year-old participants, the accuracy of recalled height and weight measured in childhood, adolescence and at ages 30 and 40 did not differ significantly from the accuracy of current self-reported height and weight that also was measured at the same time. Similarly, Norgan and Cameron 62 reported that recall of previous height and weight over a 27-to 37-year interval (measured at 18 to 24 years old) was not significantly influenced by the passage of time.…”
Section: Discussionmentioning
confidence: 99%
“…35 Others have also shown high correlations (rX0.80) between recalled and measured weight in young adulthood among middleaged and older men and women. 36,37 In the Health ABC cohort, self-reported and measured weight at study baseline (ages 70-79) was highly correlated (r ¼ 0.98). The correlation between recalled height at age 25 and measured height at study baseline was also high (r ¼ 0.93; mean difference of þ 3 cm).…”
Section: Discussionmentioning
confidence: 99%
“…17 In our study, anthropometric measurements were self-reported; however, although self-reported height tend to be overestimated and weight underestimated, [18][19][20][21] there is no reason why selfreported weight and height measures should be differently biased between cases and controls. 22 Thus, any systematic underestimation of BMI should not lead to major biases in risk estimates. Body measurements have been generally well correlated with corresponding past measurements even in older persons.…”
Section: Discussionmentioning
confidence: 99%